(untitled) (CIPEEX, 2025)
This article analyzes globalization and fundamentalism as interconnected phenomena that shape contemporary society. The study aims to understand how globalization facilitates the rapid dissemination of extremist ideologies, intensifies cultural conflicts, and contributes to the rise of religious fundamentalism. Methodologically, the research adopts a theoretical review based on the works of C.S. Lewis, Vishal Mangalwadi, Max Weber, Anthony Giddens, and Philip W. Sutton, complemented by an empirical interview with a Master Mason from the Masonic Lodge Templários do Bem nº 1498. The analysis highlights the accelerated circulation of ideas enabled by technological development, the role of charismatic leaders in mobilizing masses, and the defensive reactions of local cultures to global pressures. The results demonstrate that globalization, while fostering cultural diversity and economic opportunities, also exacerbates inequalities, challenges traditional identities, and provides fertile ground for extremism. The interview reinforces these findings, indicating how global interconnectedness exposes societies to ideological conflicts while also offering opportunities for dialogue and cooperation. The discussion emphasizes Lewis’s view of the search for spirituality in modern contexts, Mangalwadi’s defense of biblical principles as foundations for justice and human dignity, and Weber’s interpretation of charismatic authority and the "disenchantment of the world." In conclusion, the study underscores the paradox of globalization: it connects people and cultures while simultaneously destabilizing identities and stimulating fundamentalist responses. Addressing these challenges requires inclusive policies, intercultural dialogue, and a balance between global integration and the preservation of cultural and religious traditions.